Implementasi Kriptografi AES pada Sistem Enkripsi Gambar berbasis Web dengan Kunci Ephemeral yang dihasilkan API - Machfudz, Emir Syarif; Suhardi (Universitas Muhammadiyah Ponorogo, 2025)
This study implements the Advanced Encryption Standard (AES) algorithm in a web-based image encryption system utilizing an ephemeral key generated by an API. The research is motivated by the increasing threats to digital data security, such as identity theft and information manipulation, as well as the weaknesses of static key usage in AES encryption. The developed system consists of a client-side web application and a RESTful API server. The client side, built with HTML, CSS, and JavaScript, receives image input, requests the API for a key, and performs AES-256 encryption in Cipher Block Chaining (CBC) mode with a unique Initialization Vector (IV). The server side generates a random 256-bit key, stores it temporarily for approximately 30 seconds, and sends the key ID to the client. Testing was conducted on images sized 50 KB, 200 KB, and 1000 KB to measure encryption time. The results show that encryption time increases linearly with image size, with minimal overhead that does not affect performance. The ephemeral key approach enhances security by limiting the opportunity for unauthorized access to the key, while client-side encryption ensures that raw image data is never transmitted to the server. These findings demonstrate that implementing AES with ephemeral keys effectively improves the security of web-based image encryption.